Wisdom of Syria's Waiting Game : Foreign Policy Under the Assads. - Scheller, Bente (Hurst, 2014)
Syrian foreign policy, always opaque, has become an even greater puzzle during the Syrian revolt. Irrespective of the regime's international isolation in the wake of its violent response to domestic protest, it has paid lip-service to international peace plans while unperturbedly crushing the rebellion. The rare televised appearances of President Assad have shown a leader detached from reality. Has he-in his own words-'gone crazy'? In this book long- time Syria analyst and former diplomat Bente Scheller contends that Bashar Assad's deadly waiting game is following its own logic: whatever diffi.